Customer-Centric Marketing: Building Loyalty through Personalized Experiences - Heriyana, Heriyana; Nugrahaningsih , Hartanti; Abdillah , Fatimah (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study examines the impact of personalized experiences, customer satisfaction, and engagement on customer loyalty among postpaid users of Indosat, one of Indonesia’s leading telecommunications providers. Using a quantitative research design and Smart PLS for analysis, data from 258 respondents reveal that customer engagement is the most significant driver of loyalty, while personalized experiences play a critical role in enhancing customer satisfaction. The study also finds that while satisfaction contributes to loyalty, its effect is less pronounced than engagement, highlighting the importance of creating deeper emotional connections to ensure customer retention. Moreover, the moderating effect of combined satisfaction and engagement on loyalty indicates a potential diminishing return when both variables are maximized simultaneously. These findings suggest that Indosat should adopt a balanced approach that integrates personalized marketing with engagement strategies to foster long-term customer loyalty in a highly competitive market. The study contributes to the literature on customer-centric marketing by emphasizing the need for tailored and engaging customer experiences in the telecommunications sector.